Development of Interactive Learning Media Assisted by Desmos Based on RME to Improve Mathematical Representation Abilities and Resilience of Class VIII Students at SMPN 1 Idi - Astuti, Astuti; Armanto, Dian; Hasratuddin, Hasratuddin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study to describe: 1) the validity, practicality and effectiveness of the interactive learning media assisted by RME-based Desmos which was developed to increase students' mathematical representation abilities and resilience at SMP N 1 Idi; 2) increasing students' mathematical representation abilities through interactive learning media assisted by the developed RME-based Desmos; 3) increasing student resilience through interactive learning media assisted by the developed RME-based Desmos. This study is development research using the Tessmer development model, formative evaluation type. This development model consists of two development stages, namely preliminary (determination) and prototyping (design and evaluation). From the outcomes of trial I and trial II it was gotten: 1) Interactive learning media assisted by RME-based Desmos to improve students' mathematical representation abilities and resilience which was developed met the criteria of being valid, practical and effective; 2) Increasing mathematical representation abilities using interactive learning media assisted by RME-based Desmos which has been developed as seen from the N-gain value in trial I of 0.41, increasing to 0.47 in trial II, meaning it is in the "medium" category; and 3) Increasing student resilience with the RME approach that has been developed as seen from the N-gain value in trial I of 0.33, increasing to 0.51 in trial II, meaning it is in the "medium” category. Based on the study outcomes, it is recommended that teachers use interactive learning media assisted by Desmos in learning straight line equations to improve students' mathematical representation abilities and resilience.